Quantitative Strain and Compositional Studies of InxGa1−xAs Epilayer in a GaAs-based pHEMT Device Structure by TEM Techniques. (23rd April 2014) - Sridhara Rao, Duggi V.; Sankarasubramanian, Ramachandran; Muraleedharan, Kuttanellore; Mehrtens, Thorsten; Rosenauer, Andreas; Banerjee, Dipankar
Abstract: In GaAs-based pseudomorphic high-electron mobility transistor device structures, strain and composition of the In x Ga1− x As channel layer are very important as they influence the electronic properties of these devices. In this context, transmission electron microscopy techniques such as (002) dark-field imaging, high-resolution transmission electron microscopy (HRTEM) imaging, scanning transmission electron microscopy-high angle annular dark field (STEM-HAADF) imaging and selected area diffraction, are useful. A quantitative comparative study using these techniques is relevant for assessing the merits and limitations of the respective techniques. In this article, we have investigated strain and composition of the In x Ga1− x As layer with the mentioned techniques and compared the results. The HRTEM images were investigated with strain state analysis. The indium content in this layer was quantified by HAADF imaging and correlated with STEM simulations. The studies showed that the In x Ga1− x As channel layer was pseudomorphically grown leading to tetragonal strain along the [001] growth direction and that the average indium content ( x ) in the epilayer is 0.12. We found consistency in the results obtained using various methods of analysis.